COMPARATIVE ACTIVITY TESTING OF LOPERAMIDE HYDROCHLORIDUM WITH OTHER ANTIDIARE DRUG IN WHITE RATS AS AN INTRODUCTION TO DIARY - Liilis Ela Pujiati; Inang Bumulo; Arif Hidayat Arbie (Journal of Health, Technology and Science (JHTS), 2022)
Diarrhea is still a health problem, especially in developing countries including Indonesia, various kinds of drugs have been used, one of which is LoperamideHydrochloridum drug with other antidiarrheal drugs. LoperamideHydrochloridum was chosen because LoperamideHydrochloridum can inhibit intestinal motility so as to prolong intestinal transit time, reduce the frequency of defecation, increase stool viscosity and prevent electrolyte loss. This study aims to determine the usefulness or differences of several anti-diarrheal drugs, and to compare the mechanism of action of each anti-diarrheal drug used. The method used is the experimental method, the experimental method is an experiment to prove a certain question or hypothesis. Experiments can be carried out in a laboratory or outside the laboratory, experimental work implies learning to do, because it can be included in the learning method. The purpose of the experimental method is that students can design, prepare, report, implement, prove and draw conclusions from various facts and information obtained when they conduct their own experiments. The results showed that in the surgical process of rat 1, the overall length of the intestine was 65 cm and the length of the marker intestine was 30 cm. Rats 2 have a total intestine length of 67 cm with a marker intestine length of 13 cm. For rat 3, the total gut length was 37 cm and the marker gut length was 11 cm. And for 4 mice, the total intestine length was 64 cm with a marker intestine length of 47 cm.